Ahl al-Hadis and Ahl al-Ra’y (A Polemic of Domination Dynamics on Hadith) - Ansori, Ansori; Munawir, Munawir (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
In the horizon of Hadith study, two major streams have different thoughts on hadith interpretation, namely Ahl Al-Hadith and Ahl Al-Ra’y. Ahl Al-Hadith views hadith, based on their theoretical framework construction, as literal values while Ahl Al Raâ€™y, based on their knowledge, perceived hadith as contextual values. The difference in their paradigms has often put them in clashes and conflicts both on the ideological and practical levels. This study attempts to shed some light on the domination dynamics that often occur between them through historical investigation. A qualitative-interpretative method and a historical approach are applied to gain the needed data. The results show that both Ahl Al-Hadith and Ahl Al-Ra’y have existed since the time of the Prophet, the Shahaba, and the Tabi’in. In all three eras, Ahl Al-Ra’y was found more dominant than Ahl Al-Hadith. Meanwhile, Ahl Al-Hadith was recorded as dominant at the time of Imam Al-Syafi’i and during the documentation of hadiths into books. Based on these findings, it becomes clear that each of these two streams becomes a continuity base for others. Therefore, despite the domination dynamics that often occur between them, the relations of both are not addressed as antagonistic relations that nullify each other but are addressed as complementing and strengthening each other